THE EFFECTIVENESS OF PSS (PLAYS, STORIES, SONGS) METHOD IN LEARNING ENGLISH AS A FOREIGN LANGUAGE: AN EXPERIMENTAL STUDY AT STATE MADRASAH IBTIDAIYAH 1 OF PALEMBANG - Richway Richway (Tadrib: Jurnal Pendidikan Agama Islam, 2015)
The purpose of this study is to determine the effectiveness of the PSS method in teaching English as a foreign language at State Madrasah Ibtidaiyah 1 of Palembang. This study is also to determine the effect of PSS method in improving student learning outcomes.This research is a quantitative researchusingthe classes that already exist as a group, both for the experimental class and the control class, which is estimated at the same condition. The experimental study class consisted of 36 students and a control class also consists of 36 students.The result of the analysis show that the experimental class of 36 students on average score of 4.5 on the learning outcomes of pre-test and 5.97 at post-test. While the control class scored on average of 4.91 on the learning outcomes of the pre-test and 4.97 at post-test. The results of the SPSS hypothesis analysis that has been done in the paired samples t-test show that the mean of the experimental group is -1.472 with standard deviation 2.131. And t value is -4.145, while significant (2-tailed) of 0.000˂0.05. It can be concluded that rejected Ho, and can be said that there is a significant difference of students’ achievement before and after the application of PSS method.